Analisis Kinerja Simpang Bersinyal Untuk Meningkatkan Keselamatan Pada Simpang Depok Kota Depok - Widyawan, Sony; Rukman, Rukman (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2019)
The problemof transportation isone of the problems faced in Depok, especially atintersections. Problems of traffic congestion and conflicts often occur at signalizedintersections, especially at the intersection of four signalized Depok Depok City where one ofthe efforts made to reduce conflicts in Depok intersection is done by setting the intersection.The methods used in the analysis of the performance of the intersection is the use ofcalculation on IHCM, while the traffic conflict analysis to determine the level of seriousnessof traffic conflicts is by using traffic conflict Technique (TCT) is compared to that conflictVisSim 10. Recommendation is done by using a scheme using a 3-phase elections and 3.5phase and then make a comparison with the third phase (existing) and selected the mostappropriate scenario. From the scheme of recommendations that were made by using thesoftware PTV VISSIM 10 obtained the most appropriate scheme that uses three-phasearrangement. The results of the simulation phase 3 was effective at reducing the number oftraffic conflicts and service levels are still in good condition